Evaluation of the relationship between pH and titrable acidity of five different of iron supplements with the absorption of iron ions in the anterior primary teeth (an in vitro study) - Somayeh Hekmatfar; Hediyeh Piraneh; Karim Jafari (Wolters Kluwer Medknow Publications, 2018)
Background: Iron supplement is recommended for alleviating iron deficiency. Black discoloration of teeth is one of the side effects of consumption of iron supplements. Besides these effects, iron drops may also act directly on the dental hard tissues, with erosive lesions as possible outcomes of their content. In this regard, we decided to compare iron absorption of five types of iron drops in enamel and determine its relationship with pH and titrable acidity (TA) of them. Materials and Methods: In this in-vitro study The pH of 5 kinds of iron was measured by a digital pH meter. Each drop was titrated and then the TA was calculated. For this experimental study, 40 healthy anterior primary teeth were prepared and divided into 5 groups then exposed to iron drops. The level of iron absorption was determined by atomic absorption. The Pearson correlation test was used to analysis correlations between pH, TA, and absorption of iron ions in the anterior primary teeth. One-way ANOVA was used for statistical analysis. Statistical significance was set at P < 0.05. Results: The mean of pH in Kharazmi drops was significantly less than both Irovit, and FerroKids drops (P < 0.05) but did not differ significantly with other drops. Kharazmi drops TA was higher than all drops (P < 0.05). There was no significant difference between the mean iron ion adsorption, as well as between iron ion absorption with pH and TA also not found a statistically significant relationship. Conclusion: All drops have acidic content that increases their potential for erosion. Reducing the potential of the effects of iron drops on dental hard tissues should be of concern to all health professionals.